Cisco router configuration using GUI concept - Juzailah, Mohd Kheri@ Mohd Khairi (2010)
Router is one of the important devices in the network environment. It is a device that its task is to route or forward information to the destination requires in a network. All these while, the configuration of router has been done manually which is by using text-based interface or what is known as command line interface (CLI)concept. However, this method has few flaws such as time consuming, prone humanerror and not easy to understand especially by beginners. A study of router configuration has been done and found that there is a more suitable method of configuring the router which is Graphical User Interface (GUI) concept. The purpose of this project is to introduce GUI configuration on Cisco router and show its advantages. System Development Life Cycle (SDLC) will be the main methodology of this project. The system of this project will be develop using NetBeans IDE by using JAVA language and network programming. The system develop will make an easier understanding while making the configuration of the router free from human error.